Do princípio poético à poética moderna: Baudelaire entre Edgar Poe e Walter Benjamin - Santos, Paulo Henrique Alves Guerra dos (2021)
This dissertation examines the poetic principle of Charles Baudelaire, that is to say, the foundation of his poetry. It also analyses the relationship between his theory and the context in which he was involved, France of the XIX century. Firstly, in this research we seek to underline the critical reading carried out by the author in regards to Edgar Poe’s poetic theory and then we establish connections with Walter Benjamin’s reading of Baudelaire’s work. After those observations, this thesis will finally show how Baudelaire’s thought about poetry has matured over the years